Efectividad de la risoterapia en la autoestima del adulto mayor, en el centro del adulto mayor de la red asistencial de Essalud - Tarapoto Junio – Agosto 2012 - Valentine Arévalo, José Eduardo (2012)
This research study is quantitative, prospective, cuasi-experimental, made in the center of the Senior Care Network Essalud - Tarapoto, during the period June to August 2012. Aimed to determine the effectiveness of self-esteem risoterapia in elderly patients and establish, if self-esteem has psychological effects in this population. The sample consisted of 50 older adults (25 control and 25 experimental). The data collection technique used was a survey, observation guide and the questionnaire as a tool. The study showed that laughter therapy was effective in 100% in the esteem of the Elderly (p <0.05). In the control group, in the pre-test applied to determine the self-esteem of the elderly, we found that high self-esteem accounted for 32% and 68% low self-esteem, not demonstrating variability in the post test (32% high esteem); while in the experimental group shows that the number of older adults with high self-esteem increases from 24% to 100% after application of Laughter Therapy. Similarly this technique is more effective in the psychological aspect (100%) than in the social aspect (88%). It is recommended to promote the implementation of the comprehensive care Laughter Therapy in the geriatric patient, to raise their self-esteem and thus reducing morbidity and mortality from this cause, improve their mood and their social. environment.